(3GdJYhjV Yf GdMHS GdGMJjGWj aj GdJTQjY GdeUQj h GdebGQf (B/ s - (3eMeO YHO Gdehdi eMeO YHO Gdehdis; (3TQja SjO cGed s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2017)
(3JJfGhd GdOQGSI ehVhY GdMHS GdGMJjGWj, GdMHS GdGMJjGWj GdPj jLhR GdJYhjV Yfg gh GdMHS GdeNGda ddTQhW h GdVeGfGJ GdbGfhfjI, Ch ZjQ GdVQhQj dSjQ GdJMbjb, ShGA GfJaJ Yfg gPg GdVQhQI GHJOGA Ce GQJaYJ Yfg HYO Pdc; dJLGhRg GdMO GdeYbhd dUaI GdVQhQI, h jKjQ gPG GdELQGA fRGY Hjf eUdMJjf eJYGQVJjf(B: (3eUdMI GdaQO GdPi ef Mbg Cf jJeJY HMQjJg, h eUdMI GdLeGYI GdJj ef MbgG Cf JYjT aj Cef h SdGe, ceG jKjQ CjVG GdJYGQV eY CUd GdHQGAI, h jdMb VQkQG HGdkZG HGdeMHhS, ceG jUjH BNQjf ZjQg cCaQGO CSQJg, h gPG GdELQGA jhLH eSFhdjI GdCeQ Hg h eSFhdjI GdOhdI; HGYJHGQg YedkG ef CYeGd GdSdWI GdbVGFjI, h ddeVQhQ efg GdMb aj GdJYhjV GdeGOj h GdCOHj, h bO cad GdeTQY GdOSJhQj h GdELQGFj GdMb aj gPG GdJYhjV, h de jfXe MJj GdBf BdjI GdeWGdHI Hg h gh eG fgjH Hg Cf jSQY Edjg(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj (B2017.s
(3HHdjhLQGajG(B: (3UaMGJ (B629-690.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdMHS GdGMJjGWj s; (3GdWHjYI GdbGfhfjI ddMHS GdGMJjGWjs; (3GdGMcGe GdYGeI ddJYhjVs; (3eSFhdjI GdBeQ HGdMHS GdGMJjGWjs; (3GdVQQs; (3GdJYhjV GdeGOjs; (3GdJYhjV GdeYfhj s; (3GdVQQ GdCOHjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs